METHODOLOGICAL PROBLEMS OF THE COMPLEMENTARY SEMANTIC APPROACH IN TEACHING GENERAL EDUCATION SUBJECTS - Kashekova, Irina (Revista Inclusiones, 2020)
The article examines the patterns and principles of organizing the educational process in a general education school as the methodological problems of the complementary semantic approach in education, which implements the ideas of humanization and humanitarization of education. The complementary semantic approach is defined and the perspectives of the development of education in accordance with modern-day reality are identified. Owing to the fact that it combines the languages of science and art, the complementary semantic approach aims for generating different types of thinking (objective, symbolic, imaginative, creative) the synthesis of which would allow developing the independence of thinking and the skills of social adaptation and collective problem-solving. The principles of the educational process that realize all the aforementioned patterns are determined and substantiated and include spatial modeling of the educational process, mutual complementarity and intersection of science and art, interdisciplinary recursiveness, image-sign visualization, alternative solutions, associative links.